Molecular and epidemiological basis of cow's milk allergy - M. M. Fedotova; L. M. Ogorodova; O. S. Fyodorova; T. A. Evdokimova (Бюллетень сибирской медицины)
Allergy to cow's milk is characterized by early onset and high prevalence in pediatric population. The review presents current data on the molecular structure, physicochemical and allergenic properties of the cow's milk proteins. The patterns of the natural history of cow's milk allergy are described. The aspects of the development of tolerance to the proteins of this product are performed.